Cyberbullying and Depression: An empirical study of Indian executives - Sajeet Pradhan; Swati agrawal
The purpose of this paper is to investigate the linkage between cyberbullying and depression. Using the multi-mediation routes this study also explores the cyberbullying-depression relationship via helplessness and self-esteem. This study is a multi-mediation model with a sample size of 340 respondents. The study draws cross-sectional data from respondents from diverse industry backgrounds ranging from information technology, education, banking, and retail. Partial least square (PLS-SEM) was used for the analysis. Using the cognitive theory of depression, results showed that cyberbullying is positively related to depression. Also, the study found that helplessness and self-esteem mediate the linkage between cyberbullying and depression. The study is unique as perhaps for the first time the multi mediation mechanism has been studied in the relationship of cyberbullying and depression. Drawing from helplessness/ hopelessness theory, the study has conceptualized and tested cyberbullying as a stressor that triggers various adverse cognitions which have been tested in multi-mediational route. The study highlights several issues emerging with the increased use of the internet and the severe abusive behaviour in form of cyberbullying. There is a need for organizations and managers to have specific actions to reduce the tendency of helplessness and low self-esteem due to cyberbullying to control adverse cognition of depression among employees.